Maize Homologs of Hydroxycinnamoyltransferase, a Key Enzyme in Lignin Biosynthesis, Bind the Nucleotide Binding Leucine-Rich Repeat Rp1 Proteins to Modulate the Defense Response - Wang, Guan-Feng; He, Yijian; Strauch, Renee; Olukolu, Bode A.; Nielsen, Dahlia; Li, Xu; Balint-Kurti, Peter J. (Plant physiology (Bethesda), 2015)
In plants, most disease resistance genes encode nucleotide binding Leu-rich repeat (NLR) proteins that trigger a rapid localized cell death called a hypersensitive response (HR) upon pathogen recognition. The maize (Zea mays) NLR protein Rp1-D21 derives from an intragenic recombination between two NLRs, Rp1-D and Rp1-dp2, and confers an autoactive HR in the absence of pathogen infection. From a previous quantitative trait loci and genome-wide association study, we identified a single-nucleotide polymorphism locus highly associated with variation in the severity of Rp1-D21-induced HR. Two maize genes encoding hydroxycinnamoyltransferase (HCT; a key enzyme involved in lignin biosynthesis) homologs, termed HCT1806 and HCT4918, were adjacent to this single-nucleotide polymorphism. Here, we show that both HCT1806 and HCT4918 physically interact with and suppress the HR conferred by Rp1-D21 but not other autoactive NLRs when transiently coexpressed inNicotiana benthamiana. Other maize HCT homologs are unable to confer the same level of suppression on Rp1-D21-induced HR. The metabolic activity of HCT1806 and HCT4918 is unlikely to be necessary for their role in suppressing HR. We show that the lignin pathway is activated by Rp1-D21 at both the transcriptional and metabolic levels. We derive a model to explain the roles of HCT1806 and HCT4918 in Rp1-mediated disease resistance.